# How do you evaluate #12 \frac { 1} { 3} - 5\frac { 5} { 6}#?

By signing up, you agree to our Terms of Service and Privacy Policy

The answer is

or

First lets convert the mixed fractions into improper fractions (or whatever you want to call them) getting

By signing up, you agree to our Terms of Service and Privacy Policy

To evaluate (12 \frac{1}{3} - 5\frac{5}{6}), you need to subtract the two mixed numbers:

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{1}{3}) - (5 + \frac{5}{6}))

Now, find a common denominator for the fractions:

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{1}{3}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}))

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}))

Now, perform the addition and subtraction:

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = 12 + \frac{2 - 5}{6} - 5 - \frac{5}{6})

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = 12 + \frac{-3}{6} - 5 - \frac{5}{6})

Now, simplify:

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = 12 - \frac{1}{2} - 5 - \frac{5}{6})

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = 11\frac{1}{2} - 5 - \frac{5}{6})

Now, subtract:

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = 11\frac{1}{2} - 5 - \frac{5}{6} = 11\frac{1}{2} - 5 - \frac{5}{6} = 6\frac{1}{2} - \frac{5}{6})

Now, subtract the fractions:

(12 \frac{1}{3} - 5\frac{5}{6} = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = (12 + \frac{2}{6}) - (5 + \frac{5}{6}) = 11\frac{1}{2} - 5 - \frac{5}{6} = 11\frac{1}{2} - 5 - \frac{5}{6} = 6\frac{1}{2} - \frac{5}{6} = 6\frac{1}{2} - \frac{5}{6})

Convert (6\frac{1}{2}) to a fraction with a denominator of 6:

(6\frac{1}{2} = 6 + \frac{1}{2} = 6\frac{3}{6})

Now, subtract:

(6\frac{3}{6} - \frac{5}{6} = 6 - 5 + \frac{3}{6} - \frac{5}{6} = 1 + \frac{3 - 5}{6} = 1 - \frac{2}{6} = 1 - \frac{1}{3})

So, (12 \frac{1}{3} - 5\frac{5}{6} = 1\frac{1}{3}).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- Find the equivalent measures. (a) #6 1/3 ft =># ________ in (b) #5 3/4 gal=># _________ qt (c) #3 5/8 lb =># ________ oz?
- In a poll two weeks before the Presidential election, 37% of the people said they would vote for the Democrat, 42% said they would vote for the Republican, and the rest were undecided. What percent were undecided?
- How do write in simplest form given #1/2-1/3#?
- Please solve # 15 1/2 + 16 1/4 - 12 5/8 - 14 1/6 ?#
- The library has 551,984 magazines. Each bin holds 8 magazines. How many bins does the library need to hold all of its magazines?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7